(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Aluminium based composites exhibit many attractive material properties such as increased stiffness, wear resistance, specific strength and vibration damping and decreased co-efficient of thermal expansion compared with the conventional aluminium alloys. Aluminium Matrix Composites consist of non-metallic reinforcement which offers advantageous properties over base material. Reinforcements like SiC, B4C and Al2O3 are normally preferred to improve the mechanical properties. Here Aluminum LM25 is selected as matrix material while Silicon carbide and Boron carbide are selected as reinforcement material. The fabrication of aluminium matrix was done by stir casting method. In the present study an attempt has been made to investigate the effect of three major stir casting parameters (stir speed, stir duration and preheated temperature of reinforcement material) on stir casting of Aluminium LM25 - SiC - B4C composite. Experiments were conducted based on Taguchi methodology. Taguchi quality design concepts of L9 orthogonal array has been used to determine S/N ratio and through S/N ratio a set of optimum stir casting parameters were obtained. The experimental results confirmed the validity of Taguchi method for enhancing tensile strength of castings.